PENGARUH LATIHAN JUGGLING TERHADAP KEMAMPUAN MENGONTROL BOLA PESERTA EKSTRAKURIKULER SEPAKBOLA DI SMK BUKIT ASAM TANJUNG ENIM - Wahyu Ramdani; Asriansyah Asriansyah (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
The problem in this research is the lack of students 'abilities to control the ball when receiving the ball, so it needs a treatment that students' skills in mengontorol ball is not out of reach.The purpose of this study was to determine the effect of exercise on the ability to control the ball juggling extracurricular participants SMK Bukit Asam football in Tanjung Enim.This research is an experimental research study design with one group pretest and posttest design. The study collected data from 24 students as research subjects.The data collection technique is by testing and measuring using soccer instruments and holding the ball.Based on the analysis with statistical techniques, the juggling practice test obtained calculations, namely tcount = 29.529> t table = 1.713 with a significance level of 5% of 1.713,thus there is a significant effect of juggling exercises on the ability to control the ball in students participating in football extracurricular activities at Bukit Asam Tanjung Enim Vocational School